2010
DOI: 10.4269/ajtmh.2010.10-0290
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathogenesis of Epidemic and Enzootic Chikungunya Viruses in a Pregnant Rhesus Macaque Model

Abstract: Abstract. Since 2004, an East African genotype of Chikungunya virus (CHIKV) has emerged, causing significant epidemics of an arthralgic syndrome. In addition, this virus has been associated for the first time with neonatal transmission and neurological complications. In the current study, pregnant Rhesus macaques were inoculated with an enzootic or epidemic strain of CHIKV to compare pathogenesis and transplacental transmission potential. Viremias were similar for both strains and peaked at 2-3 days post-inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 43 publications
(53 reference statements)
9
57
1
Order By: Relevance
“…These data are consistent with epidemiological studies which have documented the development of protracted disease symptoms during outbreaks of CHIKV in humans involving any of the three CHIKV genotypes (5). The detection of CHIKV RNA in joint-associated tissues is also consistent with previous studies in humans in which CHIKV antigen was detected in synovial biopsy specimens collected from a patient with chronic disease (12) and in experimentally inoculated rhesus and cynomolgous macaques in which CHIKV RNA was detected in joints at later times postinoculation (22,50). Analogously, Ross River virus RNA has been detected in knee biopsy specimens collected from patients 5 weeks after the onset of joint symptoms (51).…”
Section: Discussionsupporting
confidence: 90%
“…These data are consistent with epidemiological studies which have documented the development of protracted disease symptoms during outbreaks of CHIKV in humans involving any of the three CHIKV genotypes (5). The detection of CHIKV RNA in joint-associated tissues is also consistent with previous studies in humans in which CHIKV antigen was detected in synovial biopsy specimens collected from a patient with chronic disease (12) and in experimentally inoculated rhesus and cynomolgous macaques in which CHIKV RNA was detected in joints at later times postinoculation (22,50). Analogously, Ross River virus RNA has been detected in knee biopsy specimens collected from patients 5 weeks after the onset of joint symptoms (51).…”
Section: Discussionsupporting
confidence: 90%
“…Previous to this study, direct infection of myofibers by CHIKV had not been shown, though evidence of myofiber fragmentation and necrosis has been reported (33). Since we observed the infection of myofibers following i.d.…”
Section: Discussionmentioning
confidence: 50%
“…Neonatal mice infected with the La Reunion recombinant strain (LR2006 OPY1) developed more severe disease, with progressive hind limb weakness and severe myonecrosis, than those infected with the Senegal strain (37997). 37997 and another strain from the 2006 outbreak (DHS-4263) were also compared in a macaque model, where slightly elevated viremia was seen with the 37997 strain (33). Mild muscle fiber necrosis was also seen in several animals, but muscle titers or pathology during acute infection was not determined (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations